2011
DOI: 10.1037/a0023497
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating disruptive effects of interruptions through training: What needs to be practiced?

Abstract: It is generally accepted that, with practice, people improve on most tasks. However, when tasks have multiple parts, it is not always clear what aspects of the tasks practice or training should focus on. This research explores the features that allow training to improve the ability to resume a task after an interruption, specifically focusing on task-specific versus general interruption/resumption-process mechanisms that could account for improved performance. Three experiments using multiple combinations of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 39 publications
5
41
1
2
Order By: Relevance
“…It could be that the ability to prepare for the interruption by creating a cue leads to a "cancelling" effect, trading off the benefits of a cue against the longer time away from the primary task. Consistent with this argument, an earlier study examining interruptions in an office setting did find a difference between external interruptions and internal interruptions, with external interruptions leading to more disruption (i.e., longer resumption lags) than internal interruptions (Cades, Trafton, Monk, 2011). The difference in findings may be due to features of the office environment studied.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…It could be that the ability to prepare for the interruption by creating a cue leads to a "cancelling" effect, trading off the benefits of a cue against the longer time away from the primary task. Consistent with this argument, an earlier study examining interruptions in an office setting did find a difference between external interruptions and internal interruptions, with external interruptions leading to more disruption (i.e., longer resumption lags) than internal interruptions (Cades, Trafton, Monk, 2011). The difference in findings may be due to features of the office environment studied.…”
Section: Discussionsupporting
confidence: 55%
“…The model predicts that the longer you are away from a task (i.e., the longer the interruption), the more difficult it will be to resume the task due to the lowered activation level of the primary task goal. This has been supported by several studies conducted in the laboratory (Cades, Trafton, & Monk, 2011;Hodgetts & Jones, 2006;Trafton, Altmann, Brock, & Mintz, 2003) According to the Memory for Goals theory, there are two factors that can help when activation has decayed beyond the point of being able to recall the goal. These two factors are strengthening and prim-ing.…”
Section: Theories Of Interrupted Task Performancementioning
confidence: 79%
See 1 more Smart Citation
“…To investigate the specificity of the practice effect for task/interruption pairs, Cades et al (2011) used a clever paradigm where they used two different interrupting tasks but only a single primary task. Some participants saw the same interrupting task throughout the experiment, while other participants switched interrupting tasks.…”
Section: Introductionmentioning
confidence: 99%
“…They found that participants got faster and better at resuming only when they received practice with the interruption; when the interruption was switched, there was no benefit to practice. Cades et al (2011) explained this effect by suggesting that the interrupting task primed the primary task. Resumption suffered because the priming from the interruption task is reduced when switched.…”
Section: Introductionmentioning
confidence: 99%